Assessment of Flood Vulnerability in Selected Urban Catchment (A Case Study of Uyo Metropolis, Nigeria) - NSIEGBE, Dickson Kinikawo; WELI, Vincent E; CHUKWU-OKEAH, Gift O; ELUDOYIN, Olatunde S; ABALI, Temple Probyne; INKO-TARIAH, Ibiso Michael; NKII, Lucky Baripara (Zien Journals, 2021)
Flooding occurs due to increase in global temperatures high rate of precipitation and increase rate of runoff and increase rate of urban flooding. The aim of study is to determine the flood risk assessment of selected urban catchment in Uyo metropolis, Nigeria. The study adopted correlational research design where secondary data was generated from Landsat Imageries of the study area. The digital elevation model of the area was used to determine the water shed pattern, landuse/landcover and inundation level using supervised classification of landuse in the area. The study also adopted Geographic Information System (GIS) aided computer simulation of the storm water been generated through enhanced DEM to determine storm water level and inundation based on landuse/landcover change. Data generated was analysed using hydrological models and techniques which includes storm water generation assessment, inundation modeling, assessment of land cover and level of inundation and evaluation of flash flood vulnerability using modeled inundation. Findings showed that Uyo has a number of streams of different flow lengths which was lower. The study also revealed that Uyo has 21 sub basins. The total runoff in uyo was higher (0.74) inches Also the rate of change of in catchment behaviour like the catchment precipitation, node flooding and runoff in Uyo continued to increase with time of the day, and the rate of change of volume of runoff varied slightly. The width of hydrograph was not wider as the areas prone to moderate and high flood in Uyo metropolis was higher (78.03%). Based on these findings, the study recommends that better planning of the cities is required to regulate the effect of flooding in the study area. The area liable to moderate and high flood vulnerability should be well monitored and guarded to minimize the destruction of lives and properties.
Keywords: Catchment; Flood; Urban; Vulnerability